Mott Law exp(T0/T)1/4 and Scaling Properties of the Oxygen-Deficient Tenorite CuO0.75 - Danijel Djurek; Mladen Prester; Djuro Drobac; Vilko Mandić; Damir Pajić (Condensed Matter)
The novel sub-stoichiometric copper oxide CuO0.75 was prepared via the slow oxidation of Cu2O. This compound retains the original crystallographic structure of tenorite CuO, despite the considerable presence of disordered oxygen vacancies. CuO0.75 resembles the mixed valence oxide Cu2+/Cu1+, while the unit cell contains one oxygen vacancy. Performance-wise, the electric resistivity and magnetic susceptibility data follow the Anderson–Mott localization theories. The exponential localization decay length was found to be α−1 = 2.1 nm, in line with modern scaling research. Via cooling, magnetic double-exchange interaction, mediated by oxygen, results in Zener conductivity at T~122 K, which is followed by antiferromagnetic transition at T~51 K. The obtained results indicate that the CuO0.75 compound can be perceived as a showcase material for the demonstration of a new class of high-performance magnetic materials.